On the classification of functional equations on quasigroups - Sokhats’kyi, F. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider functional equations over quasigroup operations. We prove that every quadratic parastrophically uncancelable functional equation for four object variables is parastrophically equivalent to the functional equation of mediality or the functional equation of pseudomediality. The set of all solutions of the general functional equation of pseudomediality is found and a criterion for the uncancelability of a quadratic functional equation for four object variables is established.